Further delineation of METTL23‐associated intellectual disability. Issue 4 (18th February 2020) - Almannai, Mohammed; Obaid, Osama; Faqeih, Eissa; Alasmari, Ali; Samman, Manar M.; Pinz, Hailey; Braddock, Stephen R.; Alkuraya, Fowzan S.
Abstract: METTL23 belongs to a family of methyltransferase like proteins (METTL) that transfer methyl group to various substrates. Recently, pathogenic homozygous variants in METTL23 were identified in patients from three families who presented with intellectual disability (ID) and variable dysmorphic features. In this report, we present unpublished phenotypic data from the original family as well as six new subjects from four families who also presented with mild to moderate ID and dysmorphic features, and were found to harbor four previously unpublished homozygous or compound heterozygous variants in METTL23 . Our report further supports the role of this gene in autosomal recessive ID and emphasizes the mild but consistent facial features.